2010
DOI: 10.1139/f10-088
|View full text |Cite
|
Sign up to set email alerts
|

Assessing habitat utilization and rockfish (Sebastes spp.) biomass on an isolated rocky ridge using acoustics and stereo image analysis

Abstract: For those marine fish species with specific habitat preferences, a habitat-based assessment may provide an alternative to traditional surveys. We conducted a habitat-based acoustic and stereo image stock assessment survey for rockfishes (Sebastes spp.) on a rocky ridge habitat in the eastern Bering Sea. Video analysis suggested that juvenile and adult rockfishes were more abundant on the seafloor in the rocky ridge area than on the surrounding sandy flats. Over the ridges, the distribution of rockfishes was un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
30
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 22 publications
0
30
0
Order By: Relevance
“…A range of other marine biology applications also routinely use stereoimaging techniques (photo as well as video), including: fish monitoring (Ruff et al, 1995;Van Rooij et al, 1995;Li et al, 1996;Tillett et al, 2000;Harvey et al, 2003;Costa et al, 2006;Costa et al, 2009;Rooper et al, 2010;Bower et al, 2011;Torisawa et al, 2011); determination of the 3D structure of fish schools (Cullen et al, 1965;Pitcher, 1975;Dill et al, 1981;Sawada et al, 2009); determination of the influence of substrate complexity on the interaction between fish and the artificial substrate (Fischer et al, 2007); and surveys of the benthos and the sea floor (Emerey et al, 1965;Evans and Norris, 1997;Chong and Stratford, 2002;Jasiobedzki et al, 2008;Shortis et al, 2008;Svane et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…A range of other marine biology applications also routinely use stereoimaging techniques (photo as well as video), including: fish monitoring (Ruff et al, 1995;Van Rooij et al, 1995;Li et al, 1996;Tillett et al, 2000;Harvey et al, 2003;Costa et al, 2006;Costa et al, 2009;Rooper et al, 2010;Bower et al, 2011;Torisawa et al, 2011); determination of the 3D structure of fish schools (Cullen et al, 1965;Pitcher, 1975;Dill et al, 1981;Sawada et al, 2009); determination of the influence of substrate complexity on the interaction between fish and the artificial substrate (Fischer et al, 2007); and surveys of the benthos and the sea floor (Emerey et al, 1965;Evans and Norris, 1997;Chong and Stratford, 2002;Jasiobedzki et al, 2008;Shortis et al, 2008;Svane et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Mounting evidence indicates that the presence of sponges and corals enhances structural heterogeneity in otherwise low-relief environments and can lead to increases in biodiversity and abundance of associated animals (e.g., Tissot et al, 2006; Beazley et al., 2013; Knudby et al, 2013). The morphological features of these biogenic structures may also serve as refugia for different life stages of commercially harvested species of Sebastes (Freese and Wing, 2003;Rooper and Boldt, 2005; Baillon et al, 2012) and Atka mackerel (Pleurogrammus monopterygius) (Rand and Lowe, 2011) in Alaska waters.Previous studies have also shown putative associations of rockfishes with sponge, coral, and bryozoan assemblages across a wide range of physical and oceanographic conditions (Love et al, 1991;Rooper and Martin, 2012 to concentrate near the few boulders or rocky outcrops with attached epibenthic invertebrate communities (e.g., Freese and Wing, 2003; Du Preez and Tunnicliffe, 2011). The Pacific ocean perch has been the focus of several previous studies in Alaska, and there is strong evidence that postsettlement juveniles and adults of Pacific ocean perch are found associated with sponges and corals (Krieger, 1993; Brodeur, 2001;Rooper and Boldt, 2005;Rooper et al, 2007).…”
mentioning
confidence: 96%
“…Previous studies have also shown putative associations of rockfishes with sponge, coral, and bryozoan assemblages across a wide range of physical and oceanographic conditions (Love et al, 1991;Rooper and Martin, 2012 to concentrate near the few boulders or rocky outcrops with attached epibenthic invertebrate communities (e.g., Freese and Wing, 2003; Du Preez and Tunnicliffe, 2011). The Pacific ocean perch has been the focus of several previous studies in Alaska, and there is strong evidence that postsettlement juveniles and adults of Pacific ocean perch are found associated with sponges and corals (Krieger, 1993; Brodeur, 2001;Rooper and Boldt, 2005;Rooper et al, 2007).…”
mentioning
confidence: 96%
See 2 more Smart Citations